Extreme rainfall events over the Pongola-Mtamvuna Water Management Area of South Africa - Mpungose, Nomvula Bongekile (Department of Oceanography, 2023)
Subtropical southern Africa experiences substantial rainfall variability both spatially and temporally, due to regional orography, geographic position, and local sea-surface temperatures. Extreme weather conditions such as droughts and floods are not uncommon and can result in both positive and negative socio-economic impacts. The Pongola-Mtamvuna Water Management Area (PM) located over north-eastern South Africa consists of communities that depend on rain-fed agriculture, as well as an inter-linked ecosystem and fresh water bodies that are dependent on rainfall. Extreme rainfall events and the systems that produce them are still not well understood, therefore, a detailed analysis of such events can contribute to an improved understanding and management of their associated risks. Here, the main focus is on the summer rainy season (October – March), rainfall variability is examined using CHIRPS daily rainfall data covering a period of thirty-seven years from 1981 – 2018. Extreme rainfall events are identified and classified for the PM area. The analysis points to the highest rainfall amounts typically occurring over low-lying coastal areas and near mountainous regions. About 60% of the extreme rainfall events were associated with tropical lows (40%) and MCS (20%). Cut-off lows (18%), cloud bands (16%), and tropical cyclones (6%) contributed to the remaining proportion. The highest frequency of events occurred during late summer months (January – March) when tropical lows and occasionally, tropical cyclones are more common. Rainfall over the PM has a statistically significant relationship with ENSO, most of the seasons with below-average rainfall and extreme events coincided with El Niño conditions. Odd cases where this was the opposite were more influenced by regional circulation anomalies which acted to enhance or reduce moisture over the land-mass thereby increasing conditions favourable/unfavourable for rainfall over the region.